Development of an iron diagnostic method using Malaka fruit based on digital imaging - Rismiarti, Zuri; Rahmat, Mamat; Indra, Asep Iin Nur; Hakimah, Nurul; Nurmayanti, Rani; Fadilah, Nur (Poltekkes Kemenkes Bandung, 2026)
Background: Iron (Fe) is a geochemically active element that needs to be monitored because excessive levels in water can reduce water quality and pose health risks. WHO sets a safe limit of Fe in drinking water at 0.3 mg/L. This condition demands an accurate, simple, and applicable Fe detection method without complex instruments. Objective: This study developed a digital imaging-based Fe(III) detection method using a natural reagent, malacca fruit extract, which is rich in gallic acid and forms a blue Fe-gallic acid complex. Methods: The study design included laboratory experiments involving gallic acid extraction, optimization of the Fe(III): extract ratio, optimization of measurement time, and evaluation of linearity, precision, accuracy, LoD, LoQ, and t-test against the UV-Vis spectrophotometry method. Results: The results showed an optimum Fe(III): extract ratio of 1:2, with reaction stability up to the 5th minute. A linear relationship was obtained in the range of 0.1–2 ppm (R² = 0.9969), with an LoD of 0.1377 ppm and a LoQ of 0.4589 ppm. The %RSD values ​​of 2.34–3.82% indicate good precision, while the accuracy ranges from 92.76–111.2%. A t-test confirmed that the digital imaging results were not significantly different from those of UV-Vis spectrophotometry. Conclusion: Overall, this method offers a portable, economical, and environmentally friendly analytical approach for Fe(III) detection and provides a basis for the development of digital application-based diagnostic systems using natural reagents.